A dynamic spatial CGE approach to assess economic effects of a large earthquake in China. (April 2020) - Shibusawa, Hiroyuki
Abstract: This study evaluates the economic impact of a major earthquake on regional economies in China. Our dynamic spatial computable general equilibrium model divides China into 30 regions/cities based on a multi-regional input–output table. It encompasses a decentralized economy of utility-maximizing households and profit-maximizing firms. Drawing from historical data, we simulate an unpredicted and a predicted earthquake striking China's Bohai Economic Rim and calculate the dynamic and spatial impacts before and after each. We analyze two considerations: pre-quake investments to mitigate the effects of earthquakes and post-quake expenditures to recover from them. Results show that mitigating investments accelerate economic recovery in the Bohai Rim and across all of China. This finding indicates their importance and that of spatial resilience policy in the event of an earthquake.